DJAMALUDDIN “ADINEGORO” (1904-1967): TOKOH DI BALIK PENGHARGAAN TERTINGGI JURNALISTIK DI INDONESIA - Jauhari, Fadhilah; Umasih; Syukur, Abdul (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
Djamaluddin Datuk Maradjo Sutan is an Indonesian Journalism Pioneer from Talawi, West Sumatra. However, he is better known by his pseudonym which leads to the Javanese name Adinegoro. The name Adinegoro itself was immortalized by the Indonesian Journalists Association (PWI) as the name of the highest journalism award in Indonesia since 1974. Making someone's name for an award, of course, that person has an important role in his field. Djamaluddin was the first Indonesian to study journalism directly from his home country, Germany. After returning from Europe, he is always asked or chosen to serve as a leader in a newspaper or magazine in Indonesia. Not only that, his focus on writing abroad, which always captivated readers, made him a journalist who covered the Round Table Conference in The Hague, the Netherlands at the end of 1949. Djamaluddin was also active in giving his views on the nationalization of the Aneta news agency. Djamaluddin's concern is also given to young people who want to study journalism in Indonesia. This study aims to examine the role of Djamaluddin "Adinegoro" in the world of journalism in Indonesia. The research method used is the historical or historical writing method. Djamaluddin Datuk Maradjo Sutan merupakan Pelopor Jurnalistik Indonesia yang berasal dari Talawi, Sumatera Barat. Namun ia lebih dikenal dengan nama samarannya yang mengarah ke nama Jawa yaitu Adinegoro. Nama Adinegoro sendiri diabadikan oleh Persatuan Wartawan Indonesia (PWI) sebagai nama penghargaan tertinggi jurnalistik di Indonesia sejak tahun 1974. Menjadikan nama seseorang untuk sebuah penghargaan pastinya orang tersebut memiliki peran penting dalam bidangnya. Djamaluddin adalah orang Indonesia pertama yang belajar ilmu jurnalistik langsung dari negara asalnya yaitu Jerman. Sepulangnya dari Eropa, ia selalu diminta atau dipilih menjabat sebagai pemimpin dalam surat kabar atau majalah di Indonesia. Tak hanya itu fokus penulisan luar negerinya yang selalu memikat para pembaca membuat ia terpilih menjadi jurnalis yang meliput Konferensi Meja Bundar di Den Haag, Belanda pada akhir tahun 1949. Djamaluddin juga aktif memberikan pandangannya tentang nasionalisasi kantor berita Aneta. Kepedulian Djamaluddin juga diberikan untuk kaum muda yang ingin belajar ilmu jurnalistik di Indonesia. Penelitian ini bertujuan untuk mengkaji peran Djamaluddin “Adinegoro” dalam dunia jurnalistik di Indonesia. Metode penelitian yang digunakan adalah metode penulisan sejarah atau historis.